Escherichia coli cell surface perturbation and disruption induced by antimicrobial peptides BP100 and pepR - Alves, Carla S. (2012)
This research was originally published in Journal of Biological Chemistry. Carla S. Alves… (et al.). Escherichia coli cell surface perturbation and disruption induced by antimicrobial peptides BP100 and pepR. Journal of Biological Chemistry. 2010. VOL. 285, NO. 36, pp. 27536–27544. © the American Society for Biochemistry and Molecular Biology